Synthesis, characterization and retention behavior of 4-(tetradecyloxy)-N-(4-hexyloxyphenyl)-2-hydroxybenzalimine - Cakar, F.; Yorur, C.; Cankurtaran, O.; Eran, B. Bilgin; Karaman, F. (NATL INST OPTOELECTRONICS, 2008)
A liquid crystalline compound, 4-(tetradecyloxy)-N-(4-hexyloxyphenyl)-2-hydroxybenzalimine (THPHBI) has been synthesized and characterised. Phase transition temperatures of 4-(tetradecyloxy)-N-(4-hexyloxyphenyl)-2-hydroxybenzalimine were determined by polarizing microscopy, differential scanning calorimetry and inverse gas chromatography technique (IGC). The retention diagrams of n-butyl acetate (nBA), iso-butyl acetate (IBA), benzene (B), toluene (T) and ethylbenzene (EB) were plotted between 40 and 160 degrees C by IGC. Specific retention volume, V-g(0), weight fraction activity coefficient, Omega(infinity)(1), Flory Huggins polymer-solvent interaction parameter, chi(infinity)(12), equation of state polymer-solvent interaction parameter, chi(12)* and effective exchange energy parameter, X-eff were determined for studied solvents. Then, the exchange enthalpy parameter, X-12 and entropy parameter Q(12) were determined by using a relation for the enthalpy interaction parameter, chi(*)(h) of the equation of state theory, which was arranged for the IGC.
Keywords: inverse gas chromatography; phase transition temperature; liquid crystal; interaction parameter; equation of state parameters; INVERSE GAS-CHROMATOGRAPHY; OF-STATE THEORY; POLY(DIMETHYL SILOXANE); EXCHANGE ENTHALPY; ENTROPY PARAMETERS; LIQUID-CRYSTALS; PHASE-TRANSITIONS; COMPLEXES; SOLVENTS; POLYMER; Materials Science; Optics